Universal design approach to learning: a theoretical-practical model for quality inclusive education, seen from the Postgraduate and Continuing Education Directorate of the State University of Bolívar - Chávez García, Elsita Margoth; Zula Cujano, Jorge Armando; Bósquez Barcenes, Víctor Alejandro; Pacheco Mendoza, Silvia Rosa (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Universal Design for Learning is an educational approach that seeks to provide all teachers, regardless of their abilities, with an equitable and effective learning experience. This model is based on the premise that diversity is the norm in the classroom and that students have different learning styles, abilities, and needs. Therefore, it focuses on creating flexible learning environments that can meet the needs of all students. It is based on theories, academic-scientific research, each learning environment and neuroeducation, in order to generate inclusivity in the actors of the process. In this sense, it integrates and covers the educational process, from planning to the evaluation of learning, including the reinforcement process, with the aim that teachers take advantage of various learning opportunities, in the same way that it makes teachers more flexible. the micro, meso and macro curricular design, in order to minimize limitations and unforeseen events in academic execution. Finally, it has potential both in the episteme and in praxis, facilitating academic activity and being aligned with Sustainable Development Goal 4 of the 2030 Agenda, inclusive and quality education is guaranteed, promoting learning opportunities for teachers of the education programs. master's degree in the Postgraduate and Continuing Education Department of the State University of Bolívar